In Search of Annual Legumes to Improve Forage Sorghum Yield and Nutritive Value in the Southern High Plains. Issue 1 (29th April 2016) - Angadi, Sangamesh V.; Umesh, M.R.; Contreras‐Govea, Francisco E.; Annadurai, K.; Begna, Sultan H.; Marsalis, Mark A.; Cole, N.A.; Gowda, Prasanna H.; Robert Hagevoort, G.; Lauriault, Leonard M.
Abstract : Livestock production is significant in the Southern High Plains of the United States, and demand is increasing for greater forage dry matter (DM) yield with increased nutritive value. Forage sorghum [ Sorghum bicolor (L.) Moench] (FS) is commonly used, although it is low in crude protein (CP) and high in fiber. Planting legumes with FS may improve nutritive value and/or DM yield of the harvested forage; nevertheless, only marginal improvements in CP and fiber have been reported when utilizing cowpea [ Vigna unguiculata (L.) Walp.] or lablab [ Lablab purpureus (L.) Sweet]. Consequently, additional candidate legumes must be evaluated for greater success. Irrigated studies were conducted at New Mexico State University's Agricultural Science Center at Clovis in 2 years. The experiment was a randomized complete block design replicated four times each year. Forage cowpea, lablab, Lima bean ( Phaseolus lunatus L.), and pole bean ( P. vulgaris L.) were planted between FS rows spaced at 30 inches and compared with sole FS. Lima bean mixed with FS total DM yield (6.73 tons acre −1 ) was lower than sole FS, FS‐cowpea, and FS–pole bean (7.93, 7.94, and 7.79 tons acre −1, respectively) but not FS‐lablab (7.34 tons acre −1 ). Crude protein of FS–Lima bean (7.9%) was greater than sole FS and FS–pole bean (7.0% for both) but not different from FS‐cowpea and FS‐lablab (7.4 and 7.5%, respectively). Differences in digestible DM yield followed total DM yield. Lima bean and pole bean are not viable alternatives to cowpea or lablab due to either decreased yield or lack of nutritive value improvement compared with FS forage. Consequently, the search will continue.